Carburizing steel material and producing method thereof, as well as carburized steel component

JP2025032695APending Publication Date: 2025-03-12AICHI STEEL CORP +1
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2023138123
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-28
Publication Date
2025-03-12

AI Technical Summary

Benefits of technology

【0014】 上記浸炭用鋼は、上記の特定の化学成分組成を有することを前提として、式1を満足し、後述するように製造方法に工夫を加えることにより、M7C3及びM23C6を主要な炭化物とし、かつ、上記の個数及び平均粒径の析出状態を実現したものである。このような炭化物析出状態を有している浸炭用鋼を用いることにより、その後、一般的な加熱パターンの浸炭処理(一般的な加熱パターンの高濃度浸炭処理をする場合を含む)を採用したとしても、浸炭後の炭化物析出状態を適正に制御することが可能となる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025032695000001_ABST
    Figure 2025032695000001_ABST
Patent Text Reader

Abstract

To provide a carburizing steel material capable of properly controlling a carbide deposit state after the carburization, even when a carburization treatment of a general heating pattern is adopted.SOLUTION: A carburizing steel material that has a specific range of chemical component composition satisfying the following formula 1: A=4Cr +4Mo+15V≥13.8 (where the element symbols in formula 1 indicate the content ratio (mass%) of each element), has a spheroidized structure, with a number of precipitated carbides being 200,000 pieces / mm2 or more, an average carbide particle size of 0.1 to 0.8 μm in equivalent circle diameter, and in the carbides, the total of M7C3 and M23C6 carbides accounts for 85% or more in terms of area ratio, and a hardness is 250 HV or less.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a steel material for carburizing, a manufacturing method thereof, and a carburized steel part. [Background technology]

[0002] For example, carburized steel parts that have been carburized to provide a surface-hardened layer on the surface have been used for automotive gears in order to obtain excellent strength characteristics while maintaining machinability and other workability. Measures to increase the strength of gears made of carburized steel parts have included, for example, improving the thermal softening characteristics and controlling the state of the abnormal carburized layer on the surface to obtain a running-in effect.

[0003] However, in recent years, in order to suppress vibration and noise when gears mesh, it has become necessary to improve gear precision more than ever before, and the use of a finish polishing process after carburizing has increased. If a polishing process is added, the abnormal carburized layer is removed, the running-in effect is no longer obtained, seizure and adhesion of the tooth surface becomes apparent, and surface fatigue strength is reduced.

[0004] In addition, in the electrification of automobiles, there is a demand for improved gear transmission efficiency to improve fuel economy, and there is a trend toward the use of low-viscosity oils, which are effective for this purpose, as lubricants. As the use of low-viscosity oils increases, it is expected that the oil film forming ability will decrease compared to before, which will promote seizure and adhesion.

[0005] In order to suppress these problems, it is effective not only to provide a surface hardened layer but also to finely disperse carbides in the surface layer. To achieve this, attention has been focused on high-concentration carburizing, which increases the surface carbon concentration above that achieved by normal carburizing treatment.

[0006] On the other hand, when the carbides precipitated by high-concentration carburization are coarse, the coarse carbides may become the starting points for stress concentration, which may lead to a decrease in fatigue strength. To avoid this, various methods that incorporate improvements into the carburization process have been proposed.

[0007] Patent Document 1 proposes a method for manufacturing carburized parts, which is characterized by performing primary carburizing treatment by vacuum carburizing at a temperature equal to or higher than the Acm point, followed by quenching to below the A1 point, and then performing secondary carburizing treatment by vacuum carburizing at a temperature equal to or higher than the A1 point and below the Acm point. It is said that this method makes it possible to obtain a structure in which fine carbides are dispersed in large quantities without the carbides growing coarsely.

[0008] However, the method of Patent Document 1 requires two carburizing and quenching processes, a primary carburizing and a secondary carburizing, in the carburizing process, which significantly increases the heat treatment cost compared to conventional methods, and the method is limited to vacuum carburizing. Therefore, it is not easy to adopt this method. For example, paragraph 0025 of Patent Document 1 indicates that 70% or more by volume of the fine carbides generated by the above-mentioned carburizing process are M3C type carbides.

[0009] Patent Document 2 shows that it is possible to perform low-cost high-concentration carburizing treatment on a material that has been subjected to composition adjustment for the purpose of generating fine carbides in the surface layer after high-concentration carburizing, thereby providing a steel with excellent mechanical properties such as bending fatigue strength. In a specific example, a carburizing treatment method is shown in which the material is held in a carburizing atmosphere at 950°C with a carbon potential of 1.5% or more, then cooled once to 600°C, and subsequently heated to 850°C. However, this treatment method cannot be said to be a technology that can realize the dispersion of fine carbides in a general carburizing pattern, and it is considered that there is still room for further improvement in composition adjustment.

[0010] In Patent Document 3, the Cr content is increased and the high-concentration carburizing temperature is set to a lower temperature (800-900°C) than the conventional temperature range (930-950°C), thereby achieving a (Cr,Fe) 23 C6, also known as M 23It is said that this method produces a structure in which C6 and / or (Cr,Fe)3C, so-called M3C, are finely dispersed. However, when this method is used at carburizing temperatures of 900°C or higher, which has been conventionally used, it has been shown that coarse cementite precipitates and fatigue strength decreases (paragraph 0106). Therefore, it can be said that there is still room for further improvement in the adjustment of the composition of this technology. [Prior art documents] [Patent documents]

[0011] [Patent Document 1] JP 2007-308792 A [Patent Document 2] JP 2002-266053 A [Patent Document 3] WO2011 / 114836 publication Summary of the Invention [Problem to be solved by the invention]

[0012] As described above, all of the conventional countermeasures to the problems in high-concentration carburizing treatment require carburizing treatment with a special heating pattern, and when a commonly used carburizing temperature pattern is adopted, the carbide precipitation state after carburizing cannot be optimized. The present invention has been made in view of this background, and aims to provide a carburizing steel material and a carburized steel part using the same, which are capable of appropriately controlling the carbide precipitation state after carburizing, not only when a high-concentration carburizing treatment with a common heating pattern is adopted, but also when a normal-concentration carburizing treatment with a common heating pattern is adopted, and a method for manufacturing the same. [Means for solving the problem]

[0013] One embodiment of the present invention contains, by mass%, C: 0.12 to 0.30%, Si: 0.01 to 0.90%, Mn: 0.25 to 0.90%, P: 0.030% or less, S: 0.030% or less, Cr: 2.50 to 8.00%, Mo: 0.01 to 1.00%, Al: 0.020 to 0.080%, V: 0.05 to 0.50%, N: 0.0020 to 0.0200%, and O: 0.0030% or less, As optional elements, at least one of Nb: 0.01 to 0.10%, B: 0.0005 to 0.0050%, Ti: 0.01 to 0.10%, Ca: 0.0005 to 0.0050%, Mg: 0.0005 to 0.0050, and Zr: 0.0005 to 0.0050% is contained; The balance is Fe and unavoidable impurities, and has a chemical composition that satisfies the following formula 1: Formula 1: A=4Cr+4Mo+15V≧13.8 (Note that the element symbols in formula 1 indicate the content (mass%) of each element.) It has a spheroidal structure, The number of precipitated carbides is 200,000 / mm 2 That's all. The average particle size of the carbide is 0.1 to 0.8 μm in terms of circle equivalent diameter, Among the above carbides, M7C3 and M 23 The total area ratio of C6 is 85% or more, It is a carburizing steel material with a hardness of 250HV or less. Effect of the Invention

[0014] The above carburizing steel is premised on having the above specific chemical composition, satisfies formula 1, and by making improvements to the manufacturing method as described below, it is possible to obtain M7C3 and M 23 This steel has C6 as the main carbide and has the above number and average particle size. By using carburizing steel having such a carbide precipitation state, it becomes possible to properly control the carbide precipitation state after carburizing, even if a general heating pattern of carburizing treatment (including a general heating pattern of high concentration carburizing treatment) is subsequently adopted.

[0015] As a result, when gear components are manufactured as carburized steel components using the above-mentioned carburizing steel of the present application, excellent surface fatigue strength is ensured even in cases where a finish polishing process is performed and a running-in effect cannot be obtained, which can greatly contribute to improving the transmission efficiency of gears as automobiles are increasingly electrified. [Brief description of the drawings]

[0016] [Figure 1] FIG. 2 is an explanatory diagram showing annealing treatment conditions (1) of a steel material for carburizing in an embodiment. [Diagram 2] FIG. 4 is an explanatory diagram showing annealing treatment conditions (2) of a steel material for carburizing in an embodiment. [Diagram 3] FIG. 4 is an explanatory diagram showing the annealing treatment conditions (3) of the carburizing steel in the embodiment. [Figure 4] FIG. 4 is an explanatory diagram showing annealing treatment conditions (4) of a steel material for carburizing in an embodiment. [Diagram 5] FIG. 5 is an explanatory diagram showing the annealing treatment conditions (5) of the carburizing steel in the embodiment. [Figure 6] FIG. 4 is an explanatory diagram showing an example of carburizing treatment conditions in the examples. [Figure 7] FIG. 4 is an explanatory diagram showing a preferred range in the relationship between the average grain size of carbides and the number of carbides in the examples. [Figure 8] FIG. 4 is an explanatory diagram showing a preferred range in the relationship between the A value in formula 1 and the surface carbon concentration Cs in an embodiment. [Figure 9] 4 is a SEM photograph showing the metal structure of T38 after carburization in the example. [Figure 10] 4 is a SEM photograph showing the metal structure of T12 after carburization in the example. [Figure 11] 4 is a SEM photograph showing the metal structure of T13 after carburization in the example. [Figure 12] 4 is a SEM photograph showing the metal structure of T35 after carburization in the example. [Figure 13] 1 is a SEM photograph showing the metal structure of T4 after carburization in an example. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0017] First, the reasons for limiting the chemical composition of the carburizing steel will be explained. C: 0.12~0.30%; C (carbon) is contained in an amount of 0.12% or more to ensure internal hardness, but if the C content is too high, there is a risk of deteriorating machinability, so the upper limit is set at 0.30%.

[0018] Si: 0.01-0.90%; Silicon (Si) is contained at 0.01% or more in order to improve temper softening resistance and suppress coarsening of carbides. On the other hand, if the Si content is too high, it may cause deterioration of workability and carburization resistance, so the upper limit is set at 0.90%.

[0019] Mn: 0.25~0.90%; Mn (manganese) content must be 0.25% or more to ensure internal hardness, but if the Mn content is too high, it may cause deterioration of machinability, so the upper limit is set at 0.90%.

[0020] P: 0.030% or less; P (phosphorus) is an element whose inclusion is unavoidable during manufacturing, and its inclusion as an impurity is permitted at approximately 0.030% or less.

[0021] S: 0.030% or less; S (sulfur) is an element whose inclusion is unavoidable during manufacturing, and its inclusion as an impurity is permitted at approximately 0.030% or less.

[0022] Cr: 2.50~8.00%; Cr (chromium) is an element necessary to ensure internal hardness. Furthermore, by increasing the content, M 23 It makes it easier to form carbides such as C6 and M7C3, and makes it harder to form M3C carbides that tend to become coarse. To obtain these effects, Cr is added at 2.50% or more. On the other hand, if the Cr content is too high, the effect saturates, so the upper limit is set at 8.00%.

[0023] Mo: 0.01-1.00%; Mo (molybdenum) is an element necessary for ensuring internal hardness. By increasing the content, M 23 It makes it easier to form carbides such as C6 and M7C3, and makes it harder to form M3C carbides that tend to become coarse. To obtain these effects, Mo is added at 0.01% or more. On the other hand, if the Mo content is too high, the effect saturates, so the upper limit is set at 1.00%.

[0024] Al: 0.020~0.080%; Al (aluminum) is an element used as a deoxidizer during steelmaking, and when it combines with N to exist as fine AlN, it has the effect of suppressing abnormal grain growth during carburization. To obtain these effects, the Al content is set to 0.020% or more. On the other hand, excessive addition of Al increases oxide-based inclusions such as alumina, which leads to reduced fatigue strength, so the upper limit of the Al content is set to 0.080%.

[0025] V: 0.05~0.50%; As the content of V (vanadium) increases, M 23 It makes it easier to form carbides such as C6 and M7C3, and makes it harder to form M3C carbides, which tend to become coarse. To achieve this effect, the V content is set to 0.05% or more. On the other hand, if the V content is too high, the effect saturates, so the upper limit is set to 0.50%.

[0026] N:0.0020~0.0200%; N (nitrogen) is an unavoidable element and is usually contained at 0.0020% or more. On the other hand, if the N content is too high, the workability decreases, so the upper limit is set at 0.0200%.

[0027] O: 0.0030% or less; O (oxygen) is an unavoidable element that is usually contained. However, an increase in the O content combines with Al and other elements in the steel to increase oxide-based inclusions, which leads to a decrease in fatigue strength, so the upper limit is set at 0.0030%.

[0028] Nb as optional element: 0.01-0.10%; Nb (niobium) is an optional element, but its addition refines crystal grains, increases toughness, and improves strength. When Nb is added to obtain these effects, the content must be 0.01% or more. On the other hand, if the Nb content is too high, the effect becomes saturated and the cost also increases, so the upper limit is set at 0.10%.

[0029] B as optional element: 0.0005~0.0050%; Although B (boron) is an optional element, its addition has the effect of suppressing the formation of ferrite and facilitating the formation of martensite and bainite. When B is added to obtain these effects, the content must be 0.0005% or more. On the other hand, if the B content is too high, the effect saturates and the cost also increases, so the upper limit is set to 0.0050%.

[0030] Ti as an optional element: 0.01-0.10%; Ti (titanium) is an optional element, but its addition refines crystal grains, increases toughness, and improves strength. When Ti is added to obtain these effects, the content must be 0.01% or more. On the other hand, if the Ti content is too high, the effect saturates and the cost also increases, so the upper limit is set at 0.10%.

[0031] Optional elements Ca, Mg and Zr: 0.0005-0.0050%; Ca (calcium), Mg (magnesium), and Zr (zirconium) are optional elements, but when added, they control the morphology of MnS and form a coating as an oxide on the tool surface, improving machinability. When at least one of Ca, Mg, and Zr is added to obtain these effects, the content of each element is set to 0.0005% or more. On the other hand, if the content of these elements is too high, hard oxides are formed, which may adversely affect machinability and, in the case of gears, may have an adverse effect on strength, so the upper limit for each element is set to 0.0050%.

[0032] Next, the chemical composition of the carburizing steel must satisfy the above formula 1 while containing the above elements in the above ranges. Formula 1: A=4Cr+4Mo+15V≧13.8 (Note that the element symbols in formula 1 indicate the content (mass%) of each element.)

[0033] Formula 1 shows that the addition of Cr, Mo, and V results in M7C3, M 23 This relationship was determined through many experiments, focusing on the fact that it becomes easier for C6 to form and suppresses the formation of M3C, which tends to become coarse. By adjusting the value of A in formula 1 to be 13.8 or more, it becomes easier to finely disperse carbides after carburizing.

[0034] Next, the metal structure of the carburizing steel is a spheroidal structure, and the number of precipitated carbides is 200,000 / mm 2 The average particle size of the carbide is 0.1 to 0.8 μm in terms of circle equivalent diameter, and among the carbides, M7C3 and M 23 The total of C6 is 85% or more in terms of area ratio. In order to satisfy the above-mentioned requirement of the dispersion state, it is important to adjust the value of A in the above-mentioned formula 1 to be within a range after setting the chemical components within a predetermined range.

[0035] First, the number of precipitated carbides is 200,000 / mm 2 If it is less than this, the carbides tend to become coarse during carburization, and it becomes difficult to produce a large amount of fine carbides.

[0036] In addition, if the average diameter of the carbides is less than 0.1 μm in equivalent circle diameter, they will redissolve during the carburizing heating, reducing the number of carbide formation sites, making it difficult to finely disperse them. On the other hand, if the average diameter of the carbides is more than 0.8 μm in equivalent circle diameter, and coarse carbides are precipitated, the carbides will tend to become coarser during carburizing.

[0037] In addition, there are several types of carbides that precipitate, but it suppresses the formation of cementite (M3C), which tends to precipitate coarsely on grain boundaries, and instead produces M7C3 or M 23 It is effective to actively generate C6. Among the carbides, M7C3 and M 23 It is important that the total of M7C3 and M6 is 85% or more in terms of area ratio. By satisfying this requirement together with other requirements, the large number of dispersed M7C3 and M 23 C6 functions as a carbide formation site, making it possible to finely disperse the carbides that are further generated during the carburizing process without causing them to become coarse.

[0038] In addition, the carburizing steel must have a hardness of 250 HV or less in order to ensure machinability. Furthermore, the carburizing steel is characterized in that it obtains a spheroidized structure by the annealing treatment described below. As described below, if a spheroidized structure can be obtained by an appropriate annealing treatment, it is possible to achieve a hardness of 250 HV or less.

[0039] Next, such an excellent carburizing steel material can be produced by the following method. That is, a method for producing the above-mentioned carburizing steel material, A process of heating the steel material having the above-mentioned chemical composition to 850°C or higher and hot working the steel material; Thereafter, the steel material is annealed, A method for producing a steel material for carburizing, wherein the annealing is performed under the following conditions (A) or (B). (A) The above steel material is heated to 800°C to 950°C, and then cooled at a cooling rate of 100°C / hr or less at least between 800°C and 600°C. (B) The steel material is heated to 720°C to 800°C and then cooled.

[0040] First, when manufacturing a steel material for carburizing, it is necessary to have the specific chemical composition described above, and furthermore, to satisfy the above formula 1. If formula 1 is not satisfied, cementite (M3C) is likely to form and grow during annealing treatment, even if the annealing conditions after hot working are devised, and it becomes difficult to uniformly disperse carbides as formation sites before carburizing. Therefore, it is very important that the above formula 1 is satisfied.

[0041] In addition, before annealing, the steel material is heated to 850°C or higher and hot worked to obtain the desired rough shape. If the heating temperature is less than 850°C, the deformation resistance increases and processing may become difficult. Therefore, the heating temperature is preferably 850°C or higher. The upper limit of the heating temperature is preferably 1250°C. If the temperature is higher than this, the processing cost increases while the effect of the temperature increase is not obtained.

[0042] After hot working a steel material having a chemical composition that satisfies formula 1, it is important to anneal it under the above condition (A) or (B).

[0043] The condition of (A) is to heat the steel material to a temperature (800°C to 950°C) where all or at least a part of the metal structure becomes an austenite structure, and then to cool it at a cooling rate of 100°C / hr or less at least between 800°C and 600°C, thereby suppressing the formation of M3C while forming M7C3 and M 23 C6 can be dispersed uniformly in large quantities.

[0044] In this case, the annealing temperature is in the range of 800°C to 950°C. After heating and holding in this temperature range, it is essential to set the cooling rate to 100°C / hr or less until the temperature reaches 600°C. If this cooling condition cannot be selected, there is a possibility that a spheroidized structure cannot be obtained or that an appropriate carbide precipitation state cannot be ensured. In addition, if the annealing temperature exceeds 950°C, there is a problem that the effect is not commensurate with the cost required for heating. On the other hand, if the annealing temperature is less than 800°C, there is no need to particularly control the cooling conditions, and the condition (B) can be adopted.

[0045] The condition (B) is to heat the steel material to a temperature (720-800°C) that does not exceed the A3 transformation point, and then to cool it. This also suppresses the formation of M3C while forming M7C3 and M 23 C6 can be uniformly dispersed in large quantities. Also, a spherical structure can be obtained, as in the case of (A).

[0046] In this case, if the annealing temperature is less than 720°C, there is a problem that the elements are not sufficiently diffused and the dispersion of the carbides becomes insufficient, and if it exceeds 800°C, as described above, it becomes difficult to obtain the desired carbide precipitation state unless specific cooling conditions are met.

[0047] Next, examples of carburized steel parts manufactured using the above-mentioned excellent carburized steel material include the following. That is, the alloy contains, by mass%, C: 0.12-0.30%, Si: 0.01-0.90%, Mn: 0.25-0.90%, P: 0.030% or less, S: 0.030% or less, Cr: 2.50-8.00%, Mo: 0.01-1.00%, Al: 0.020-0.080%, V: 0.05-0.50%, N: 0.0020-0.0200%, and O: 0.0030% or less. As optional elements, at least one of Nb: 0.01 to 0.10%, B: 0.0005 to 0.0050%, Ti: 0.01 to 0.10%, Ca: 0.0005 to 0.0050%, Mg: 0.0005 to 0.0050, and Zr: 0.0005 to 0.0050% is contained; The balance is Fe and unavoidable impurities, and has a chemical composition that satisfies the following formula 1: Formula 1: A=4Cr+4Mo+15V≧13.8 (Note that the element symbols in formula 1 indicate the content (mass%) of each element.) The surface has a hardened layer due to carburization. At least a part of the outermost surface of the surface-hardened layer has a finished surface that has been subjected to a finish polishing treatment; The surface hardened layer is formed at a depth of 50 μm from the finished surface. Hardness is 720HV or more. The area ratio of retained austenite is 50% or less, The carbon concentration after carburization (Cs) and A in the above formula 1 satisfy the following formula 2, Formula 2: (A+95) / 100 ≦ Cs ≦(7×A+95) / 100 The average grain size of carbides having a circle equivalent diameter of less than 5 μm is 1.0 μm or less, The area ratio of coarse carbides with a circle equivalent diameter of 5 μm or more is 10% or less, The area ratio of total carbide is 3 to 50%. There is a carburized steel part in which the main carbide type is M7C3, which accounts for more than 50% of the total carbides in terms of area ratio.

[0048] The carburized steel part is manufactured by using the above-mentioned carburizing steel material and subjecting it to at least a carburizing treatment with a general heating pattern, and has a surface-hardened layer on its surface. At least a part of the outermost surface of this surface-hardened layer is provided with a finished surface that has been subjected to a finish polishing treatment. For example, in the case of gears, a finished surface is provided in which an abnormal carburized layer has been removed by finish polishing in order to reduce vibration and noise. A finished surface that has been subjected to a finish polishing treatment can be confirmed by a person skilled in the art by observing the properties of the surface, without having to consider the method. The characteristics of this carburized steel part are as described above, as characteristics specified at a depth of 50 μm from the finished surface that has been subjected to the finish polishing treatment.

[0049] First, the surface hardness after carburizing is 720HV or more. This makes it easy to ensure high levels of fatigue strength and other strength properties. In addition, by making the area ratio of retained austenite 50% or less, it is possible to prevent problems that occur when a large amount of retained γ (austenite) is generated in the surface layer, such as a decrease in surface hardness and strength.

[0050] Moreover, it is essential that the carburized steel part has a carbon concentration after carburization (Cs) and A in the above formula 1 satisfy the following formula 2. Formula 2: (A+95) / 100 ≦ Cs ≦(7×A+95) / 100

[0051] Generally, if the surface carbon concentration (Cs) after carburization is low, the amount of carbides formed is reduced and sufficient strength cannot be obtained. On the other hand, if the surface carbon concentration (Cs) after carburization is high, coarse M3C is easily formed, resulting in reduced strength. In addition, the state of carbide formation changes depending on the Cr, Mo, and V content (A in formula 1), which makes it difficult to form M3C, and the higher the content of these elements, the more the amount of M3C formed is suppressed and fine carbides (M7C3, M 23 This relationship is shown in Equation 2, and it is important to satisfy this relationship. In terms of manufacturing, it is important to control the carburizing conditions appropriately to control Cs and satisfy Equation 2.

[0052] In addition, it is desirable that the state of the carbides in the carburized steel parts is such that there are few coarse carbides and many fine ones are dispersed. To achieve this, it is necessary that the average grain size of carbides with a circle equivalent diameter of less than 5 μm is 1.0 μm or less, the area ratio of coarse carbides with a circle equivalent diameter of 5 μm or more is 10% or less, the area ratio of all carbides is 3 to 50%, and further that the main carbide type is M7C3, accounting for 50% or more of the total carbides in terms of area ratio. Note that although the main carbide type is M7C3, some carbides are M 23 C6 is also fine.

[0053] For example, if M7C3 accounts for less than 50% of the total carbides and M3C becomes the main carbide type, sufficient strength improvement effect cannot be obtained, and the number of coarse carbides increases, which may result in failure to satisfy the other requirements mentioned above, resulting in a decrease in strength. Therefore, it is necessary that the main precipitated carbide is M7C3, not M3C.

[0054] By thus providing all of the above-listed properties, the carburized steel part can exhibit excellent properties, and can have excellent fatigue strength properties, etc., even in a state in which it has been finish-polished like modern gears.

[0055] Next, in order to manufacture the above-mentioned excellent carburized steel parts, it is not necessary to carry out any special carburizing treatment, such as the two carburizing treatments described in the above-mentioned prior application, but rather it is sufficient to carry out the conventional carburizing treatment once.

[0056] Specifically, the conditions are not necessarily limited to those below, but for example, after a carburizing and diffusion period in which the material is held in a carburizing gas atmosphere at a temperature of 900°C to 950°C for 75 to 400 minutes, Hold at 700-900°C for 15-60 minutes, followed by This can be done by quenching in oil at 50 to 150°C. The carburizing treatment can be performed with a carbon potential in the range of 0.60 to 1.20, which includes both the conventional carburizing treatment at a normal concentration level and the high concentration carburizing treatment.

[0057] If the carbon potential CP is set too low, it becomes difficult to finely disperse a large number of carbides, and if it is too high, it will cause the formation of M3C, which tends to coarsen, and the formation of retained austenite, which will lead to a decrease in strength, so by adjusting the value to an appropriate level so that the carbides are appropriately dispersed, it is possible to manufacture carburized steel parts with excellent performance. Note that the carbon potential CP setting is not always constant, and can be set with a certain degree of freedom, such as starting from a value higher than the target Cs and then lowering it halfway to a value equivalent to Cs.

[0058] In addition, the above carburized steel parts can be subjected to shot peening, which is a treatment conventionally known to improve fatigue strength, and the effects of plastic deformation and the generation of processing-induced martensite can be used to increase the compressive residual stress on the surface and improve the bending fatigue strength, so that the application of shot peening can have an effect of improving bending fatigue strength, particularly in parts that require high strength. However, in the area where the finish polishing process is performed, the shot peened surface is removed by polishing, but in the case of gears, for example, areas that require high bending strength in actual use, such as the base of the teeth, and that do not come into contact with the surface of the mating gear, are not subjected to finish polishing for improving surface fatigue strength, but are left in the shot peened surface state, with high compressive residual stress remaining on the surface (hereinafter, this area is referred to as the bending fatigue strength strengthening area), which can have a significant effect on improving bending fatigue strength.

[0059] In this way, a carburized steel part manufactured by further performing a shot peening treatment after carburizing treatment using the above-mentioned excellent carburizing steel material has improved properties compared to a carburized steel part without shot peening. The part of the surface hardened layer of the part, which has a finished surface that has been finish-polished, contributes to an excellent improvement in surface fatigue strength, and the part having a shot surface that has not been finish-polished and is only shot peened, becomes a bending fatigue strength strengthened region that ensures high compressive residual stress, and the presence of this region makes it possible to make a carburized steel part that can contribute to ensuring excellent bending fatigue strength. Note that a shot surface as it has been shot peened can be confirmed by a person skilled in the art by observing the properties of the surface without having to consider the method.

[0060] That is, the alloy contains, by mass%, C: 0.12-0.30%, Si: 0.01-0.90%, Mn: 0.25-0.90%, P: 0.030% or less, S: 0.030% or less, Cr: 2.50-8.00%, Mo: 0.01-1.00%, Al: 0.020-0.080%, V: 0.05-0.50%, N: 0.0020-0.0200%, and O: 0.0030% or less. As optional elements, at least one of Nb: 0.01 to 0.10%, B: 0.0005 to 0.0050%, Ti: 0.01 to 0.10%, Ca: 0.0005 to 0.0050%, Mg: 0.0005 to 0.0050, and Zr: 0.0005 to 0.0050% is contained; The balance is Fe and unavoidable impurities, and has a chemical composition that satisfies the following formula 1: Formula 1: A=4Cr+4Mo+15V≧13.8 (Note that the element symbols in formula 1 indicate the content (mass%) of each element.) The surface has a hardened layer due to carburization. At least a part of the outermost surface of the surface-hardened layer has a shot surface that is as it is after the shot peening treatment and a finished surface that has been subjected to a finish polishing treatment, The surface hardened layer is formed at a depth of 50 μm from the finished surface. Hardness is 720HV or more. The area ratio of retained austenite is 50% or less, The carbon concentration after carburization (Cs) and A in the above formula 1 satisfy the following formula 2, Formula 2: (A+95) / 100 ≦ Cs ≦(7×A+95) / 100 The average grain size of carbides having a circle equivalent diameter of less than 5 μm is 1.0 μm or less, The area ratio of coarse carbides with a circle equivalent diameter of 5 μm or more is 10% or less, The area ratio of total carbide is 3 to 50%. The main carbide type is M7C3, which accounts for 50% or more of the total carbides in terms of area ratio. The maximum compressive residual stress value of the shot surface of the surface hardened layer is 1000 MPa or more.

[0061] The carburized steel part that has been subjected to this shot peening treatment has a shot surface that is not finish polished and remains as shot peened in a part of the surface consisting of a surface hardened layer due to carburizing. The part with this shot surface functions as a bending fatigue strength strengthening area with a maximum compressive residual stress of 1000 MPa or more, and as described later, the bending fatigue strength characteristics are further improved. The shot surface part that has not been finish polished has a slightly improved surface hardness and a slightly decreased amount of retained austenite compared to before the shot peening treatment, and it may be possible to achieve, for example, a surface hardness of 820 HV or more and a retained austenite area ratio of 30% or less. EXAMPLES

[0062] An explanation will be given of examples relating to the above-mentioned carburized steel material, carburized steel parts using the same, and methods for manufacturing the same.

[0063] <Steel for carburizing> As shown in Table 1, 26 types of steel (steel types A to Z) with different chemical compositions were prepared, and when producing steel for carburizing from these steels, the manufacturing conditions were changed to produce 38 types of steel for carburizing (Test Nos. T1 to T38), as shown in Tables 2 and 3 described below.

[0064] In manufacturing the steel material for carburizing, an ingot of the above steel material was prepared, and then it was forged and processed into a shape of φ32 mm × L600 mm, and then heated and held at 1200°C to simulate the processing history of a gear, and then cooled, and then annealed. The annealing conditions were any of the five conditions (1) to (5) described below, as shown in Tables 2 and 3.

[0065] As shown in Fig. 1, the annealing condition (1) is a condition in which the steel material is heated to 900°C and held there for one hour, then moved into a furnace held at 620°C, held at that temperature for one hour, and then allowed to cool naturally or in the furnace. This is an example in which the steel material is cooled at a cooling rate exceeding 100°C / hr when moved from a temperature held state of 900°C into a furnace held at 620°C and cooled.

[0066] As shown in FIG. 2, the annealing conditions (2) are as follows: the steel is heated to 900°C and held there for 1 hour, then cooled to 600°C over 4 hours at a cooling rate of 75°C / hr, and then allowed to cool naturally or in a furnace.

[0067] As shown in FIG. 3, the annealing treatment condition (3) is to heat the steel material to 760°C and hold it there for 4 hours, then cool it to 600°C over 8 hours at a cooling rate of 20°C / hr, and then cool it naturally or in a furnace.

[0068] As shown in FIG. 4, the annealing treatment condition (4) is a condition in which the steel material is heated to 850°C and held there for 4 hours, then cooled to 790°C over 3 hours, held at that temperature for 3 hours, and then cooled to 600°C at a cooling rate of 15°C / hr, and then allowed to cool naturally or in a furnace.

[0069] As shown in FIG. 5, the annealing treatment condition (5) is a condition in which the steel material is heated to 760° C. and held at that temperature for 4 hours, and then allowed to cool.

[0070] Among the above annealing conditions, (2) and (4) correspond to the annealing condition (A), (3) and (5) correspond to the annealing condition (B), and (1) does not correspond to either (A) or (B).

[0071] <Structural observation of carburizing steel> The φ32mm cross section of the carburizing steel obtained by the above-mentioned various annealing treatments was mirror-polished, then corroded with picral, and SEM photographs were taken at 5000x magnification. An image analyzer was used to identify the metal structure and to measure the number of carbides, average grain size, and area ratio. The carbides were identified by measuring the diffraction pattern using SEM-EBSD and carrying out crystal phase analysis. The structure, main carbides, and M7C3 and M 23 Area ratio of C6, M7C3 and M 23 M for the sum of C6 23 The measurement results of the area ratio of C6 and the area ratio of M7C3, the average grain size of all carbides, and the number of all carbides are shown in Tables 2 and 3.

[0072] <Hardness measurement of carburizing steel> Hardness measurements were performed at a depth of D / 4 (D: test piece diameter) from the surface of the obtained carburizing steel. The hardness measurements were performed in accordance with the Vickers hardness test - test method of JIS Z 2244 (2017). The load was 10 kgf, and measurements were performed five times for each test piece, with the average value being the measured value. The measurement results are shown in Tables 2 and 3.

[0073] [Table 1]

[0074] [Table 2]

[0075] [Table 3]

[0076] <Carburized steel parts> The above-mentioned steel material for carburizing was subjected to cutting processing to prepare the following test pieces for evaluating bending fatigue strength and test pieces for evaluating surface fatigue strength, which were then subjected to carburizing treatment to obtain carburized steel parts.

[0077] The test piece for evaluating bending fatigue strength was a cylindrical test piece with a circular cross section and a diameter of φ10 mm, in which a notch with a notch depth of 1.0 mm and a notch curvature radius of 1.0 mm was provided.

[0078] The test piece for evaluating the surface fatigue strength was a small roller for the roller pitting test described later, having an outer diameter of 26 mm and a width of 28 mm, and was manufactured by machining from the above carburizing steel.

[0079] The carburizing conditions for the bending fatigue strength evaluation test pieces and surface fatigue strength evaluation test pieces were as follows: in the carburizing and diffusion period, they were held at a temperature T in the range of 880 to 950°C for 300 minutes in a carburizing gas atmosphere, then held at the pre-quenching temperature of 850°C for 30 minutes, and quenched in oil at 60°C, as shown in Figure 6. The carburizing and diffusion period temperatures, CP (carbon potential), and other conditions were adjusted as shown in Tables 4 and 5. After carburizing, each test piece was subjected to a tempering treatment in which it was held at 150°C for 1 hour and then allowed to cool.

[0080] After the carburizing, quenching and tempering processes, each test piece was given a finishing process for the parts that would become the gripping parts in each test. In addition, to simulate the gear grinding process, which is equivalent to the final polishing process, a grinding process was carried out on the outermost surface of the hardened surface layer, with a removal allowance of 100 μm.

[0081] <Observation of the structure of carburized steel parts> To quantify the structure of the carburized steel parts, the center of the 26 mm outer diameter part of the test piece for surface fatigue strength evaluation was cut, the cross section was mirror-polished, and then etched with picral. A scanning electron microscope photograph was taken at a magnification of 5000 times at a position 50 μm from the surface, and the number of carbides, average grain size, and area ratio were measured using an image analyzer. The carbides were identified by measuring the diffraction pattern using SEM-EBSD and analyzing the crystal phase. Tables 4 and 5 show the area ratio of the main carbides, the area ratio of M7C3 in all carbides, and the area ratio of non-M7C3 carbides, the average grain size in all carbides, the area ratio of all carbides, and the area ratio of coarse carbides with a circle equivalent diameter of 5 μm or more.

[0082] <Measurement of surface carbon concentration (Cs) of carburized steel parts> The cross section of the test piece subjected to the above-mentioned structure observation was mirror-polished, and the carbon concentration at a position 50 μm from the surface was measured by EPMA. The results are shown in Tables 4 and 5.

[0083] <Hardness measurement of carburized steel parts> The hardness of the carburized steel parts was measured by mirror polishing the cross section of the test piece that had been subjected to the above-mentioned structure observation, and measuring the Vickers hardness (test load: 300 g) HV at a position 100 μm from the surface. The results are shown in Tables 4 and 5.

[0084] <Measurement of retained austenite amount in carburized steel parts> The amount of retained γ (austenite) in the carburized steel parts was measured by electrolytic polishing up to 50 μm from the surface center of the 26 mm outer diameter part of the test piece for evaluating contact fatigue strength, and then the measurement was performed by XRD. The results are shown in Tables 4 and 5.

[0085] <Bending fatigue strength test of carburized steel parts> The bending fatigue strength of the carburized steel parts was measured by the Ono-type rotating bending fatigue test using the above-mentioned test pieces for bending fatigue strength evaluation. The test was performed at a rotation speed of 3600 rpm for 10 7 The bending fatigue strength was determined as the strength at which the specimens were subjected to bending fatigue tests. Test pieces with a bending fatigue strength of 500 MPa or more, which is the strength of the carburized SCM420 general-purpose steel, were evaluated as excellent (○), and those with a bending fatigue strength below 500 MPa were evaluated as poor (×). The results are shown in Tables 4 and 5.

[0086] <Surface fatigue strength test of carburized steel parts> The surface fatigue strength of the carburized steel parts was measured by a roller pitting test using the small roller as the test piece for evaluating the surface fatigue strength described above. The large roller used in the test was a SUJ2 quenched and tempered product with a crowning of 150R. The test was carried out under the following conditions: rotation speed: 2000 rpm, lubricant: AT oil, oil temperature: 120°C, slip ratio: -40%, and the strength at 10 million cycles was defined as the surface fatigue strength. Products with a surface fatigue strength below 3400 MPa were rated as inferior (×), since a sufficient strength improvement could not be expected compared to the carburized SCM420 steel, which is a general-purpose steel, and products with a surface fatigue strength of 3400 MPa or more were rated as excellent (○). The results are shown in Tables 4 and 5.

[0087] In Tables 2 to 5, an overall judgment is given as to whether the expected effects of the present invention have been obtained, with a pass (◯) or a fail (×). Tables 2 and 3 show the overall judgment results before carburization, while Tables 4 and 5 show the overall judgment results after carburization.

[0088] <Confirmation of the effect of shot peening on carburized steel parts> In the above-described tests, evaluation was basically performed without shot peening, but in order to confirm the effect of shot peening on the bending fatigue strength improvement of the carburized steel parts of the present application, shot peening was performed on test pieces (after carburizing) for evaluating bending fatigue strength prepared under the same conditions as T4, T12, T18, T22, and T32 among the test materials, and an experiment was performed to confirm the effect on bending fatigue strength. Note that the shot peening was performed using shot grains with a diameter of 0.6 mm in the first step under the condition of an arc height of 0.3 to 0.6 mmA, and using shot grains with a diameter of 0.05 mm in the second step under the condition of an arc height of 0.1 to 0.3 mmA (coverage was 100% or more for both the first and second steps).

[0089] The shot peening treatment of the surface hardened layer after carburizing of the test piece for evaluating bending fatigue strength was performed without finish polishing of the surface hardened layer, and no finish polishing was performed after the shot peening treatment. Since the shot peening treatment affects the surface hardness and the amount of retained austenite and imparts high compressive residual stress, the surface hardness, the area ratio of retained austenite, and the maximum compressive stress value were confirmed after the shot peening treatment. In addition, a fatigue test was performed using the test piece for evaluating bending fatigue strength after the shot peening treatment (rotating bending fatigue test piece), and the bending fatigue strength was compared with that without the above-mentioned shot peening treatment. The maximum compressive residual stress value was also measured for the test piece without the shot peening treatment. The results are shown in Table 6.

[0090] <Maximum compressive residual stress measurement> The maximum compressive residual stress was measured using a micro X-ray residual stress analyzer (PSPC: manufactured by Rigaku Corporation). The test piece for evaluating bending fatigue strength was electrolytically polished from the surface to a specified depth (depth greater than or equal to the depth at which the maximum value of compressive residual stress can be measured), while the residual stress was measured sequentially. The measurement conditions were collimator diameter: φ1mm, measurement location: central position in the axial direction, measurement direction: circumferential direction. The maximum value of the above measurement results was taken as the maximum compressive residual stress value.

[0091] [Table 4]

[0092] [Table 5]

[0093] [Table 6]

[0094] As can be seen from Tables 2 to 5, the alloy has the above-mentioned specific chemical composition range, satisfies formula 1, has a spheroidized metal structure, and has a number of precipitated carbides of 200,000 / mm2 or more, the average grain size of the carbides is 0.1 to 0.8 μm in terms of circle equivalent diameter, and among all the carbides, M7C3 and M 23 It can be seen that for carburized steel materials (Test Nos. T2-4, T6-8, T10-12, T14-32) in which the total of C6 is 85% or more in area ratio and the hardness is 250HV or less, even if a process such as secondary quenching described in the above patent documents is not carried out and carburized under general conditions, it is possible to obtain carburized steel parts with excellent strength characteristics having a metal structure in which M7C3 is finely precipitated as the main carbide while suppressing the generation of coarse carbides.

[0095] Furthermore, as can be seen from Table 6, it was confirmed that the test specimens that were subjected to the shot peening treatment had a higher compressive residual stress than the test specimens that were not subjected to the shot peening treatment, and as a result, the bending fatigue strength was further improved.

[0096] For T1 and T9, the chemical composition was appropriate, but the annealing conditions after hot working were inappropriate (condition (1)), and therefore the carbides could not be dispersed properly. In addition, the hardening effect occurred, and the steel became a carburizing steel material with a structure mainly composed of martensite. As a result, the hardness was too high and the workability was poor. It was determined that further evaluation was unnecessary, and no carburizing treatment was performed.

[0097] T5 and T13 had appropriate chemical composition and the carbide precipitation state was appropriate for carburizing steels, so there were no problems. However, the carburizing atmosphere conditions were not appropriate, and as a result, the surface carbon concentration (Cs) after carburizing was too high and fell into the range that did not satisfy Equation 2. In addition, the carbides in the resulting carburized steel parts were inappropriate, being mainly M3C, resulting in inferior bending fatigue strength and surface fatigue strength.

[0098] T33 does not contain at least Mo and V in its chemical composition and does not satisfy formula 1. In the carburizing steel, the precipitated carbides are M7C3 and M 23The total area ratio of C6 was below 85% and the average grain size exceeded 0.8μm. Therefore, in the state of carburized steel parts obtained by carburizing under normal conditions, the main carbide type was not M7C3, but there was an increase in M3C, which is easily coarsened, so the average grain size exceeded 1.0μm and the area ratio of coarse carbides exceeded 10%, resulting in poor bending fatigue strength and surface fatigue strength.

[0099] T34 does not contain at least V in its chemical composition and does not satisfy formula 1. In the carburizing steel, the precipitated carbides are M7C3 and M 23 The total area ratio of C6 was below 85%, and the amount of M3C, which tends to coarsen, increased, with the average grain size exceeding 0.8μm. Therefore, in the state of carburized steel parts obtained by carburizing under general conditions, the main carbide type was not M7C3, but there was an increase in M3C, which tends to coarsen, so the average grain size exceeded 1.0μm and the area ratio of coarse carbides exceeded 10%, resulting in poor bending fatigue strength and surface fatigue strength.

[0100] In the chemical composition of T35, the Cr content was too low, so it did not satisfy formula 1, and in the carburizing steel it formed a ferrite-pearlite structure, and an appropriate carbide state was not obtained. As a result, in the state of carburized steel parts obtained by carburizing under general conditions, the main carbide type was M3C, which is easily coarsened, with an average grain size exceeding 1.0 μm and an area ratio of coarse carbides exceeding 10%, resulting in poor bending fatigue strength and surface fatigue strength.

[0101] In the chemical composition of T36, the C content was too high and the Cr content was too low, so it did not satisfy formula 1, and the steel for carburizing had a ferrite-pearlite structure and did not have an appropriate carbide state. As a result, in the state of carburized steel parts obtained by carburizing under general conditions, the main carbide type was M3C, which is easily coarsened, with an average grain size exceeding 1.0 μm and an area ratio of coarse carbides exceeding 10%, resulting in poor bending fatigue strength and surface fatigue strength.

[0102] In the chemical composition of T37, the C content was too low, resulting in a small number of carbides in the carburizing steel. As a result, the low C content reduced the internal strength of the carburizing steel, and even after carburizing, although there was no problem with the carbide precipitation in the carburized steel parts, the impact of the insufficient C content on strength was large, resulting in inferior bending fatigue strength and surface fatigue strength.

[0103] In the chemical composition of T38, the Si content is at least too high, and there is no problem with the carbide precipitation state in the carburizing steel material. However, in the state of carburized steel parts obtained by carburizing under general conditions, the Si content is too high, which reduces the carburizing ability, Cs does not increase as expected, the area ratio of precipitated carbides is too low, the surface hardness is also low, and the bending fatigue strength and surface fatigue strength are poor.

[0104] Incidentally, before carburization, T38 satisfies the conditions of the present invention in terms of hardness and carbide precipitation state, and if it were simply evaluated as is, the evaluation before carburization would be pass (O); however, taking into consideration its poor carburization properties, it is recorded as fail (X) in Table 3.

[0105] Next, the appropriate ranges for the average grain size and number of carbides in carburizing steel are shown in Figure 7. The figure plots the average grain size (μm) of carbides in carburizing steel on the horizontal axis and the number of carbides (pieces / mm 2 ) is plotted on the vertical axis, and T1 to T38 (excluding T1, T9, T35, and T36) that satisfy formula 1 are indicated with the symbol "◯" and those that do not are indicated with the symbol "×".

[0106] As can be seen from the figure, by adjusting the composition to satisfy formula 1, the number of carbides can be increased to 200,000 / mm 2The carbide dispersion state can be adjusted so that the average grain size is 0.8 μm or less. Then, an appropriate carbide dispersion state can be achieved by the subsequent carburizing process. If the average grain size is less than 0.1 μm, the carbides will re-dissolve during the carburizing heating, reducing the number of carbide generation sites and making it difficult to finely disperse them, so 0.1 μm is set as the lower limit. In Figure 7, the value of formula 1 is ◯, but there is one example with a small number of carbides. This is an example where there is no problem with the carbide dispersion state, but the required number of carbides could not be generated due to the low C content.

[0107] Next, the relationship between the surface carbon concentration after carburization (Cs) and the value of A in formula 1 is shown in Figure 8. In this figure, the horizontal axis is the value of A in formula 1, and the vertical axis is the surface carbon concentration after carburization (Cs), and the results are plotted for T1 to T38 (excluding T1, T9 and T37), with those that passed the overall judgment marked with a "○" and those that failed marked with an "×".

[0108] As can be seen from the figure, the necessary conditions for obtaining excellent carburized steel parts overall are that Cs falls between line L1 representing the left side of equation 2 and line L2 representing the right side of equation 2, and that the value of A in equation 1 is 13.8 or more.

[0109] Next, the typical structure state after carburizing treatment will be explained using SEM photographs. Figure 9 shows the structure of T38 after carburization. It can be seen from the figure that the amount of carbide precipitated is small. As can be seen from Table 5, this is because the Si content is too high, which reduces the carburizing ability and lowers the Cs content.

[0110] Figure 10 shows the structure of T12 after carburization. It can be seen from the figure that many fine carbides are dispersed, and that an ideal carbide state has been obtained. This is because, as can be seen from Table 2, the carbide precipitation state of the carburizing steel is in a good state within the range specified in this invention, and by using this carburizing steel, Cs is controlled within an appropriate range, resulting in an appropriate carbide precipitation state, even when carburizing is performed under general conditions.

[0111] Figure 11 shows the state of the structure of T13 after carburizing. It can be seen from the figure that a large number of coarse carbides have formed. This is thought to be because, although the carbide precipitation was not problematic before carburizing, the carburizing treatment was performed under conditions that resulted in a surface carbon concentration that did not satisfy formula 2, resulting in an increase in M3C carbides, which are prone to coarsening.

[0112] Figure 12 shows the structure of T35 after carburizing. It can be seen from the figure that coarse carbides have precipitated. As can be seen from Tables 1, 3 and 5, this is an example where the Cr content was too low (steel type W) and formula 1 was not satisfied, so ideal carbide precipitation was not achieved at the carburizing steel stage. Therefore, when general carburizing treatment was performed, coarse carbides mainly consisting of M3C were precipitated, resulting in a decrease in strength properties.

[0113] Figure 13 shows the structure after carburizing of T4. It can be seen from the figure that a large number of fine carbides are dispersed, and that an ideal carbide state has been obtained. This is thought to be because, as can be seen from Tables 1 and 2, the Cr content is appropriately high (steel type A), which satisfies formula 1 and results in a good carbide precipitation state in the carburizing steel, and as a result of the carburizing process being carried out on this carburizing steel so that the surface carbon concentration would satisfy formula 2, an appropriate carbide precipitation state was obtained after carburizing, even though the carburizing process itself was not a special process but a general carburizing process. [Explanation of symbols]

[0114] L1 Line showing the left side of Equation 2 L2 Line showing the right side of Equation 2

Claims

1. In mass%, it contains C: 0.12 to 0.30%, Si: 0.01 to 0.90%, Mn: 0.25 to 0.90%, P: 0.030% or less, S: 0.030% or less, Cr: 2.50 to 8.00%, Mo: 0.01 to 1.00%, Al: 0.020 to 0.080%, V: 0.05 to 0.50%, N: 0.0020 to 0.0200%, and O: 0.0030% or less, As optional elements, at least one of Nb: 0.01 to 0.10%, B: 0.0005 to 0.0050%, Ti: 0.01 to 0.10%, Ca: 0.0005 to 0.0050%, Mg: 0.0005 to 0.0050, and Zr: 0.0005 to 0.0050% is contained; The balance is Fe and unavoidable impurities, and has a chemical composition that satisfies the following formula 1: Formula 1: A=4Cr+4Mo+15V≧13.8 (Note that the element symbols in Formula 1 indicate the content (mass%) of each element.) It has a spheroidal structure, The number of precipitated carbides is 200,000 / mm 2 That's all. The average particle size of the carbide is 0.1 to 0.8 μm in terms of circle equivalent diameter, Among the above carbides, M 7 C 3 and M. 23 C 6 The total of the above is 85% or more in terms of area ratio, A carburizing steel material having a hardness of 250HV or less.

2. A method for producing the carburizing steel material according to claim 1, comprising the steps of: A step of heating the steel material having the above-mentioned chemical composition to 850°C or higher and hot working the steel material; Thereafter, the steel material is annealed, The method for producing a steel material for carburizing, wherein the annealing is performed under the following conditions (A) or (B). (A) The steel material is heated to 800°C to 950°C, and then cooled at a cooling rate of 100°C / hr or less at least between 800°C and 600°C. (B) The steel material is heated to 720°C to 800°C and then cooled.

3. In mass%, it contains C: 0.12 to 0.30%, Si: 0.01 to 0.90%, Mn: 0.25 to 0.90%, P: 0.030% or less, S: 0.030% or less, Cr: 2.50 to 8.00%, Mo: 0.01 to 1.00%, Al: 0.020 to 0.080%, V: 0.05 to 0.50%, N: 0.0020 to 0.0200%, and O: 0.0030% or less, As optional elements, at least one of Nb: 0.01 to 0.10%, B: 0.0005 to 0.0050%, Ti: 0.01 to 0.10%, Ca: 0.0005 to 0.0050%, Mg: 0.0005 to 0.0050, and Zr: 0.0005 to 0.0050% is contained; The balance is Fe and unavoidable impurities, and has a chemical composition that satisfies the following formula 1: Formula 1: A=4Cr+4Mo+15V≧13.8 (Note that the element symbols in Formula 1 indicate the content (mass%) of each element.) The surface has a hardened layer due to carburization. At least a part of the outermost surface of the surface-hardened layer has a finished surface that has been subjected to a finish polishing treatment; The surface hardened layer is formed at a depth of 50 μm from the finished surface. Hardness is 720 HV or more, The area ratio of retained austenite is 50% or less, The carbon concentration after carburization (Cs) and A in the above formula 1 satisfy the following formula 2, Formula 2: (A+95) / 100 ≦ Cs ≦ (7×A+95) / 100 The average grain size of carbides having a circle equivalent diameter of less than 5 μm is 1.0 μm or less, The area ratio of coarse carbides having a circle equivalent diameter of 5 μm or more is 10% or less, The area ratio of all carbides is 3 to 50%; The main carbide type is M 7 C 3 wherein the area ratio of the carbides is 50% or more of the total carbides.

4. In mass%, it contains C: 0.12 to 0.30%, Si: 0.01 to 0.90%, Mn: 0.25 to 0.90%, P: 0.030% or less, S: 0.030% or less, Cr: 2.50 to 8.00%, Mo: 0.01 to 1.00%, Al: 0.020 to 0.080%, V: 0.05 to 0.50%, N: 0.0020 to 0.0200%, and O: 0.0030% or less, As optional elements, at least one of Nb: 0.01 to 0.10%, B: 0.0005 to 0.0050%, Ti: 0.01 to 0.10%, Ca: 0.0005 to 0.0050%, Mg: 0.0005 to 0.0050, and Zr: 0.0005 to 0.0050% is contained; The balance is Fe and unavoidable impurities, and has a chemical composition that satisfies the following formula 1: Formula 1: A=4Cr+4Mo+15V≧13.8 (Note that the element symbols in Formula 1 indicate the content (mass%) of each element.) The surface has a hardened layer due to carburization. At least a part of the outermost surface of the surface-hardened layer has a shot surface that is as it is after the shot peening treatment and a finished surface that has been subjected to a finish polishing treatment, The surface hardened layer is formed at a depth of 50 μm from the finished surface. Hardness is 720 HV or more, The area ratio of retained austenite is 50% or less, The carbon concentration after carburization (Cs) and A in the above formula 1 satisfy the following formula 2, Formula 2: (A+95) / 100 ≦ Cs ≦ (7×A+95) / 100 The average grain size of carbides having a circle equivalent diameter of less than 5 μm is 1.0 μm or less, The area ratio of coarse carbides having a circle equivalent diameter of 5 μm or more is 10% or less, The area ratio of all carbides is 3 to 50%; The main carbide type is M 7 C 3 The area ratio of the carbides is 50% or more of the total carbides, A carburized steel part, wherein the maximum compressive residual stress value of the shot surface of the surface hardened layer is 1000 MPa or more.

Citation Information

Patent Citations

  • Carburizing steel

    JP2002266053A

  • Carburized component and manufacturing method thereof

    JP2007308792A

  • Steel for case-hardening treatment, case-hardened steel component, and method for producing same

    WO2011114836A1